El intelectual y la política. Manuel González Prada y su proyecto político (1886-1903) - Rosario, Emilio (2018)
Proposes to demonstrate the construction of a political project having as central axis the figure of Manuel González Prada in the framework of the intense cultural activity that developed this intellectual. It distinguishes two moments: the first, from 1886 to 1903; The second, from 1904 to 1909. It postulates that in the first stage it travels from the criticism of the political scenario of the postwar Pacific with the Constitution of the political project which aspires to the Presidency of the Republic, towards the second, which desists from that purpose and assumes an anarchist position.